Disappearing dissent? Repression and state consolidation in Mexico. (March 2018) - Osorio, Javier; Schubiger, Livia I; Weintraub, Michael
Does violent repression strengthen the state? In this article we explore the legacies of repression by the Mexican government on subsequent patterns of state consolidation. We investigate how a particular form of state repression, forced disappearances of alleged leftist dissidents during the 'Dirty War', had path-dependent consequences for different dimensions of state capacity nearly 50 years later. To do so, we rely on data gathered from suppressed Mexican human rights reports of forced disappearances which, to our knowledge, have not been analyzed by social scientists before. Controlling for a rich set of pre-disappearances covariates we find that forced disappearances are positively correlated with contemporary measures of fiscal, territorial, and bureaucratic capacity. However, historical forced disappearances do not help the state to provide security, to consolidate its monopoly over the use of force, or to provide welfare-related public goods in the long run. Moreover, disappearances are negatively correlated with various measures of trust in the government. Forced disappearances committed by the state appear to have long-term yet heterogeneous effects on state consolidation.